Analisis Putusan Pengadilan Pajak atas Penyerahan Casing & Tubing High Grade Ditinjau dari Compliance Cost & Kebijakan Perpajakan di Free Trade Zone Batam - Armando, Tupa Andri; Rosdiana, Haula (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
This research aims to analyze Tax Court Decision is not in accordance with evidences and provisions of tax law and regulation. This research aims also explains standing of Branch Offices and Head Office. In legal provisions, Branch Office is part of Head Office. For simplicity of administration, Head Office and Branch Office are separate entities in fulfilling Tax Obligations referred to Article 12 paragraph (1) of VAT Law, including for purposes of tax invoices. Conclusion from this research is Agreement signed by Head Office with PT Pertamina EP in Jakarta, and also Invoice issued from Head Office to PT Pertamina EP could not be assessed that the person who make submission was Head Office. We need see substance of goods carried out from Batam, Evidence of news event handover of goods show that transfer of rights of taxable goods by Branch Office to PT Pertamina in Batam, and customs documents indicating that PT Pertamina as the owner of goods from since Batam.